Protein transport into peroxisomes: Knowns and unknowns - Francisco, T (2017)
Peroxisomal matrix proteins are synthesized on cytosolic ribosomes and rapidly transported into the organelle by a complex machinery. The data gathered in recent years suggest that this machinery operates through a syringe-like mechanism, in which the shuttling receptor PEX5 - the “plunger” - pushes a newly synthesized protein all the way through a peroxisomal transmembrane protein complex - the “barrel” - into the matrix of the organelle. Notably, insertion of cargo-loaded receptor into the “barrel” is an ATP-independent process, whereas extraction of the receptor back into the cytosol requires its monoubiquitination and the action of ATP-dependent mechanoenzymes. Here, we review the main data behind this model.